Antarctica: Sonic Reckonings Essay - Carolyn Philpott (2015)
Sonic Reckonings draws together contemporary compositions by five composers from two countries on opposite sides of the globe (the United States of America and Australia) who are united in their fascination with the sounds and environment of the world’s southernmost continent, Antarctica. All five composers – Lawrence English, Cheryl Leonard, Jay Needham, Douglas Quin and Philip Samartzis – have visited the far south for at least one austral summer and then returned to their homelands with numerous field recordings and myriad ideas relating to how to share their experiences, in sonic terms, with an audience consisting primarily of people who have never been down to the ice. This concert, which connects with the theme of the Balance-Unbalance 2015 international conference (“Water, Climate, Place: Re-Imagining Environments”) in a multitude of ways, provides a rare opportunity to listen to these composers’ personal experiences and perceptions of Antarctica – the sounds of a place that for many centuries remained an unknown, imagined environment.